Polemik Peranan Bin (Badan Intelijen Negara) dalam Menangani Pandemi Covid-19 - Puji Sari Mardalena; Gili Argenti; Moch. Faizal Rizki (Jurnal Ilmiah Wahana Pendidikan, 2022)
The State Intelligence Agency (BIN) as one of the organizers of public safety is considered not to have the power to be involved in handling the Covid-19 pandemic. The various exercises carried out are considered to have the potential to abuse their authority and are counter-beneficial for inter-agency cooperation in limiting the spread of Covid-19. Through an illustrative subjective methodology, this exploration will describe the oddities through disclosing and describing accounts of suspicious information and exercises carried out by BIN in dealing with Covid-19. Given the four main components provided by Law no. 17/2011, in particular (1) the existence of insight data; (2) important investigations; (3) the existence of an expected hazard; and (4) there is a shield against the public interest and security, the assumption that BIN's contribution will be dissected and thoroughly examined. The consequence of this research shows that there are complexities and changes in hazards that place more emphasis on human security, thus enabling BIN to control the dangers that interfere with the welfare of citizens.